Effect of Immersion Duration and Meat Thickness of Soaked Meat in Liquid Smoke on Physical and the Sensory Quality of Beef - Noviana Adis Amalia; Sutaryo Sutaryo; Agung Purnomoadi (JURNAL ILMIAH PETERNAKAN TERPADU, 2021)
The aim of this study was to evaluate the effect of immersion duration and meat thickness of soaked meat in liquid smoke on the physical and sensory quality of beef. This experiment used Longisimus dorsi of Simmental bull beef that slaughtered at two years old. The observed variables were pH value, cooking loss and beef sensory properties (beef appearance, aroma, tenderness and flavour). The pH value and cooking loss data were analyzed of variance (Anova)  at 5% significance level. The Duncan Multiple Range Test was applied when there was significant effect of treatment on pH and coking loss. Beef sensory properties data were Anova at 5% significance level and followed by Mann Whitney Test when there was significant effect of treatment on the observed variables. The result showed that there was no interaction (P>0.05) between immersion duration and meat thickness on all observed variables. The immersion duration gave a significant effect (P<0.05) on the pH value, beef appearance, aroma, and flavour while meat thickness gave a significant effect (P<0.05) on meat tenderness. There was no significant effect (P>0.05) of immersion duration and meat thickness on cooking loss. In conclusion, panelists prefer meat that soaked in liquid smoke for five minutes.